1987
DOI: 10.1016/0005-2736(87)90164-7
|View full text |Cite
|
Sign up to set email alerts
|

Melittin induces HII phase formation in cardiolipin model membranes

Abstract: The interaction of melittin with bovine heart cardiolipin model membranes was investigated via binding assays, 3t P-NMR, freeze-fracture electron microscopy, small angle X-ray diffraction and fluorescence based fusion assays. A strong binding (K d < 10-7 M) appeared to be accompanied by the formation of large structures, resulting from a fusion process of extremely fast initial rate. As the melittin content is increased, bilayer structure is gradually lost and from a cardiolipin to melittin ratio of about 6 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 60 publications
5
45
0
Order By: Relevance
“…This difference is a first indication suggestive of a deeper penetration in the cardiolipin system, though it should be kept in mind that depth of penetration and blue shift of fluorescence are not directly related. The fluorescence changes reach a plateau value at a phospholipid to melittin ratio of 2.03 + 0.07 : 1, which is in good agreement with the stoichiometry established with a centrifugation based binding assay [1]. The K a was calculated to be (1.6 + 0.7).…”
Section: Melittin Purificationsupporting
confidence: 84%
See 4 more Smart Citations
“…This difference is a first indication suggestive of a deeper penetration in the cardiolipin system, though it should be kept in mind that depth of penetration and blue shift of fluorescence are not directly related. The fluorescence changes reach a plateau value at a phospholipid to melittin ratio of 2.03 + 0.07 : 1, which is in good agreement with the stoichiometry established with a centrifugation based binding assay [1]. The K a was calculated to be (1.6 + 0.7).…”
Section: Melittin Purificationsupporting
confidence: 84%
“…The vast majority of these reports were limited to the insertion of melittin into detergent micelles or phosphati- dylcholine bilayers. Our 3ap-NMR, freeze-fracture and X-ray diffraction studies however, as reported in the preceding article [1] show a remarkable difference between the structural alterations induced by melittin in the negatively charged cardiolipin system (formation of inverted non-bilayer structures) and those reported for phosphatidylcholines (formation of disc and micellar type of structures [16,19]). The hypothesis that this lipid specific structural reorganization is correlated with a different mode of insertion is addressed in this report, using fluorescence techniques.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations